Architecture of the banking system of Ukraine under destructive challenges - Ukhnal, Nataliia; Bublyk, Yevhen; Brus, Svitlana; Klymenko, Kateryna (Public Finance Quarterly, 2025)
This study examines Ukraine’s banking system architecture amid unprecedented destructive challenges including geopolitical tensions, macroeconomic instability, and technological advancements. Using systemic and institutional approaches with statistical and analytical methods, we evaluate the banking system’s capacity for self-organization and adaptation. Results indicate Ukraine’s banking system demonstrates dual nature—rapid adaptation to external shocks while remaining vulnerable to prolonged crises. Institutional flexibility emerges as crucial for enhancing resilience, with adaptability manifested through structural reconfiguration and proactive risk management. Analysis of the Financial Stress Index reveals how military aggression, exchange rate volatility, and macroeconomic factors affect financial stability. International financial organizations play a vital role through external funding and regulatory standards implementation. Government support, particularly the “5-7-9%” program, has effectively provided financing for SMEs with 69,691 loans totaling 273.1 billion of UAH issued during martial law. The research develops conceptual frameworks for strategic banking system adaptation based on seven complementary approaches that collectively enhance the sector’s institutional capacity amid uncertainty.